2015
DOI: 10.1039/c5tb00401b
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-loaded PEO–PPO–PCL/TPGS mixed micelles for overcoming multidrug resistance and enhancing antitumor efficacy

Abstract: A schematic diagram of DTX-loaded PEO–PPO–PCL/TPGS mixed micelles in vivo for overcoming multidrug resistance and enhancing antitumor efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Docetaxel (DTX) is one of the first-line anticancer drugs for solid tumours and is an antimitotic agent used in the cell cycle to promote tubulin polymerization and impede cells in the G2-M phase. [22,23] Nevertheless, its clinical application remains limited by low solubility, serious side effects, drug resistance and poor specificity. [24] The emergence of MDR has led to the failure of DTX in the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Docetaxel (DTX) is one of the first-line anticancer drugs for solid tumours and is an antimitotic agent used in the cell cycle to promote tubulin polymerization and impede cells in the G2-M phase. [22,23] Nevertheless, its clinical application remains limited by low solubility, serious side effects, drug resistance and poor specificity. [24] The emergence of MDR has led to the failure of DTX in the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed micelles showed negligible hemolytic potential (less than 5 %) to red blood cells (RBCs) even at the highest concentration of 2 mg mL −1 , which demonstrated that mixed micelles were blood‐compatible and safe for intravenous administration as well as their potential to be a drug delivery system. The excellent blood biocompatibility could be attributed to the outermost PEG shell, which serves as a protective layer …”
Section: Resultsmentioning
confidence: 90%
“…The excellentb loodb iocompatibility could be attributed to the outermost PEG shell,whichserves as aprotective layer. [28,29]…”
Section: Ex Vivo Hemolysis Assaysmentioning
confidence: 99%
“…In the process of micellization, CMC was a key index to evaluate self-aggregation ability of micelles. The aggregation behavior of the material LC-SA/CS-SA in aqueous media was determined by fluorescence probe technique using pyrene as fluorescence probe (Shi et al, 2015). The curve of I 1 /I 3 value vs. the logarithmic concentration of the micelle material LC-SA/CS-SA is shown in Figure 5(A).…”
Section: Determination Of Cmcmentioning
confidence: 99%